The influence of perchlorate on the growth and yield of Cucumis Sativus in a hydroponic system [microform] - Uys, Jacobus Wilhelm (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1996.